Design and fabrication of MIG welding jigs - Wong, Fei Yong (2011)
This thesis deals with the design and fabrication of MIG welding jigs. The objective of this thesis is to develop welding jigs that able to clamp workpiece and reduce the deflection due to thermal stress. At the same time, the welding jigs also able to clamp workpiece with the thickness up to 8mm and 80 mm width. Clamping design and common welding jigs material was studied in order to design and generate concept for the MIG welding jigs. Solid Works was used to design or draw the final concept of the MIG welding jigs. The material used to fabricate these welding jigs is aluminium block. On the other hand, screw clamp was used to design clamping system for the welding jigs. The welding jigs were design in such an order that it able to adjust the gap between workpiece and give out the gap measurement so that the time taken for the welding research can be reduced. Methods and process involve in accomplish this is the machining process by using conventional milling machine, cutting process by using the vertical bend saw, joining process by using screwing, welding process and filing process.